Strategic Management of Higher Education: A Study on Increasing the Number of New Students at University X - Dharmajaya, Muhamad Agung; Rachman, Nono Arief; Raharja, Arif Budi (Educenter : Jurnal Ilmiah Pendidikan, 2025)
The increase in the number of new students is one indicator of the success of universities in facing increasingly fierce competition in higher education. This study aims to analyze the implementation of strategic management in an effort to increase the number of new students at University X. This study uses a qualitative approach with descriptive methods, where data is collected through interviews, observations, and documentation studies regarding the planning, implementation, and evaluation of new student admission strategies. The results show that University X implements various strategies, including digital and offline promotion and marketing, strengthening the branding of highly accredited study programs, improving the quality of lecturers and academic services, providing incentives and appreciation for students and the academic community, supporting Student Activity Units, routine monitoring, and data analysis based on tracer studies and registration data. The implementation of appropriate and sustainable strategies, including adjustments based on evaluations, has been proven to increase the attractiveness of institutions in the eyes of prospective students and support the increase in the number of new students. This study emphasizes the importance of implementing consistent, adaptive, and data-driven strategic management to maintain the sustainability and competitiveness of universities.